The Determinants of Import Demand: A Review of International Literature : Array - Vacu, Nomfundo; Odhiambo, N.M. (Acta Universitatis Danubius. Œconomica, 2020)
This paper provides a review of theoretical and empirical literature on the key determinants of import demand in developing and developed countries. On the whole, the findings of the studies reviewed in this paper show that the determinants of import demand differ from country to country and over time, and depend on the proxies used to measure import demand. Also, the findings confirmed that the key drivers of import demand depend on whether the income variable is used as a single variable or is disaggregated into different components. In general, the majority of the studies found that income and relative import price are the key determinants of import demand – although the nature of the impact of these factors differs from country to country.